PHOS PHATE TREATMENT OF FROZEN PRAWNS II. FROZEN STORAGE CHARACTERISTICS OF PRAWN MEAT TREATED WITH POLY PHOSPHATES - MATHEN, CYRIAC (Fishery Technology, 2025)
This communication reports the changes in physical, organa=Jeptic and biochemical characteristics of prawn meat dip-treated withalkaline and neutral solutions of polyphosphates during frozenstorage. Results are presented on changes in thawed and cookedyields, Water extractable nitrogen, non-protein nitrogen, free cx:aminonitrogen, salt solubility, myosin and moisture in the muscleand loss of soluble nitrogenous constituents in thaw drip duringfrozen storage upto seven months. The salt solubility remainedunchanged during storage in samples treated with neutral polyphosphatesolutions and the organoleptic quality was superior to controlsample. It is concluded that dip treatment with neutralised solutionsof tripolyphosphate not only maintains correct drained weight andimproves cooked yield during prolonged frozen storage but alsoprotects the frozen product from denaturation as measured by thesalt solubility of the proteins.INTRODUCTION